Communicative Action Notation with Shared Storage - Musicante, Martin; Mosses, Peter D. (DAIMI Report Series, 1993)
A variation of the Communicative Action Notation is presented, in order to allow the sharing of storage among agents. Examples of use of the new notation are given by means of the description of semaphores, monitors and RPC mechanisms. The operational semantics of the new notation is also presented.